The Economic Burden of Families with Autism Spectrum Disorders (ASD) Children in Malaysia - Sazlina Kamaralzaman; Hasnah Toran; Suziyani Mohamed; Nazmin Binti Abdullah (Journal of ICSAR, 2018)
The economic burden of families with Autism Spectrum Disorders (ASD) children that are far beyond the needs of typical children causes physical and mental stress for their parents. The study aims to examine the economic burden of parents with ASD children in Malaysia. Calculation is made using a cost-loss approach due to ASD that include direct, indirect and developmental costs. Using convenient sampling method, a total of 245 parents have filled out questionnaires through online or hard copies. Development costs represent the highest cost of RM20,989.33, followed by medical direct costs RM8,378.73, RM5,033.57 for non-medical direct costs and RM963.99 for indirect costs. The total cost of financing an ASD child is RM35,365.62 a year. This is a huge and burdensome amount for parents. The findings of this study may assist responsible parties in the planning of effective service provision to suit the need of parents with ASD children in Malaysia.